Hydrodeoxygenation of guaiacol as a model compound of lignin-derived pyrolysis bio-oil over zirconia-supported Rh catalyst: Process optimization and reaction kinetics. (1st March 2019) - He, Yifeng; Bie, Yuwei; Lehtonen, Juha; Liu, Ronghou; Cai, Junmeng
Graphical abstract: Highlights: Deoxygenation of guaiacol with the synthesized Rh/ZrO2 catalyst was achieved. High yield of oxygen-free product (87.7mol%, cyclohexane) was obtained. The suitable reaction conditions were 5 wt.% guaiacol, 300 °C, 7 MPa and 3 h. Kinetics at four temperatures fit well to a pseudo-first-order kinetic model. Abstract: To explore the mechanism for hydrodeoxygenation (HDO) of bio-oil, which contains large compounds that share similar molecular structures of phenyl ring with oxygen-containing functional groups, guaiacol as a typical model compound of lignin-derived bio-oil was hydrotreated at 150–350 °C under 3–7 MPa (H2 ) using the synthesized zirconia-supported Rh catalyst in a batch reactor. With Rh/ZrO2 catalyst, guaiacol can be completely converted where reaction temperature plays a decisive role and significantly affects the degree of hydrogenation. HDO Process was optimized with insight into effects of different reaction parameters, including H2 pressure, reactant concentration, reaction time and temperature, on the whole process of HDO and formation of undesired oxygen-contained products. The optimum reaction conditions were 5 wt. % guaiacol, 300 °C and 7 MPa in which guaiacol could be completely deoxygenated with 87. 7 mol% oxygen-free product of cyclohexane in 3 h and the desired O/C and H/C ratios of products were obtained. A specific reaction network including three main steps: "guaiacol → 1-methyl-1, 2-cyclohexanediol → cyclohexanone and cyclohexanol → completely deoxygenated compounds of cycloalkanes", was deduced by a comprehensive study on different reaction parameters and a typical key reaction network for HDO of lignin-derived bio-oil is proposed based on model compounds studies. Kinetic model for HDO of guiaacol with the Rh/ZrO2 catalyst was proposed based on the credible pathway and it fits well to a pseudo-first-order kinetic model that the R 2 values obtained for the fittings were all above 0.98 at four temperatures. At low temperature of 150 °C, the kinetically relevant step is hydrogenation of the aromatic ring, yielding 90 mol% 1-methyl-1, 2-cyclohexanediol, while at high temperature (≥300 °C), the kinetically relevant step is the complete deoxygenation of oxygen-containing functional groups which mainly yields cyclohexane. These results would be helpful to further understand the HDO mechanism of lignin-derived bio-oil, and the excellent performance of Rh/ZrO2 demonstrated its potential application in bio-oil hydrodeoxygenative upgrading process.